A NEW CONTROL STRATEGY FOR HIGHLY EFFICIENT PHOTOVOLTAIC SINGLE PHASE GRID CONNECTED INVERTER SYSTEM USING PARTIAL POWER CONVERTERS - Balachander, K.; S, Ashok Kumar. (International Journal of Psychosocial Rehabilitation, 2019)
An advanced power control strategy by limiting the maximum feed-in power of PV systems has been proposed, which can ensure a fast and smooth transition between maximum power point tracking with Partial Power Converter (PPC) and Phase Locked Loop and Current Controller (PLL-CC) method. Regardless of the solar irradiance levels, high-performance and stable operation are always achieved by the proposed control strategy. It can regulate the PV output power according to any set-point and force the PV systems to operate at the left side of the maximum power point without stability problems. The effectiveness of the proposed PPC control in terms of high accuracy, fast dynamics, and stable transitions improvement. Overall power management unit is controlled by the converter & control loop. Performance analysis (power & stability) of the overall system is carried out.The study has been carried out using MATLAB/SIMULINK model.